Pengaruh Persepsi Harga dan Desain Produk terhadap Keputusan Pembelian Konsumen : Survei pada CV. Syahdan Dwi Asia Ciamis - Eneng Nurhasanah (CV. Ulil Albab Corp, 2022)
The purpose of this research is to find out, firstly the perception of price, product design, and consumer purchasing decisions on CV. Syahdan Dwi Asia Ciamis, both the effect of price perception and product design simultaneously on consumer purchasing decisions CV. Syahdan Dwi Asia Ciamis, and the third effect of price perception and product design partially on consumer purchasing decisions CV. Syahdan Dwi Asia Ciamis. The method used in this research is a quantitative method with a survey approach. The results of the study indicate price perceptions, product design, and consumer purchasing decisions on CV. Syahdan Dwi Asia Ciamis was very kind. There is a simultaneous significant effect of price perception and product design variables on purchasing decisions at CV. Syahdan Dwi Asia Ciamis. There is a partially significant effect of price perception variables on purchasing decisions at CV. Syahdan Dwi Asia Ciamis. There is a partially significant effect of product design variables on purchasing decisions at CV. Syahdan Dwi Asia Ciamis.